Tuberculosis Research Trends in Indonesian Health Scientific Journals: From Research Design to Data Analysis - Nita Yunianti Ratnasari; Sri Handayani (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
This study aims to analyze various tuberculosis articles that have been published in health scientific journals in Indonesia. These involve the frequency of the number of publications per year, type of research, research subjects, and topics that are often raised by the researchers in their research. This research method used the principle of content analysis which focused on findings from various studies on tuberculosis that have been published in scientific journals in Indonesia. Data were collected from content analysis in journals related to tuberculosis. The results of the journal’s content analysis published in SINTA-1 with the tuberculosis subject area in the last ten years as a whole show the progress from year to year. There are four things that become the subjects of study analysis, namely the number of publications per year (the publication of tuberculosis articles in the SINTA 1 journal decreased in 2019 because of the emergence of the Coronavirus in that year and began to plague in the following years); research type (in this study the results obtained that of the 27 articles analyzed, 23 of them were quantitative types). Subject (tuberculosis patients sampled in this study included the intensive phase and the advanced phase patients) and research topic (topics around knowledge are still the variables that researchers are most interested in).